2022
DOI: 10.3390/cells11060930
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Differentially Influences the Survival and Metabolism of Cells in the Melanoma Microenvironment

Abstract: The cellular composition of the tumor microenvironment, including tumor, immune, stromal, and endothelial cells, significantly influences responses to cancer therapies. In this study, we analyzed the impact of oxidative stress, induced by cold atmospheric plasma (CAP), on tumor cells, T cells, and macrophages, which comprise part of the melanoma microenvironment. To accomplish this, cells were grown in different in vitro cell culture models and were treated with varying amounts of CAP. Subsequent alterations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Buffy coats were obtained from healthy volunteers, and macrophages were isolated from them as previously described [ 31 ]. In brief, 150 million peripheral blood mononuclear cells (PBMC) were plated in RPMI1640 (Thermo Fisher Scientific, #31870, Waltham, MA, USA), containing 1% Glutamax (Thermo Fisher Scientific, #35050038) and 0.1% Primocin (InvivoGen, #ant-pm-2, San Diego, CA, USA) in cell culture Petri dishes (Corning, #430167, Corning, NY, USA) for at least 1 h in a 37 °C 5% CO 2 incubator to promote attachment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Buffy coats were obtained from healthy volunteers, and macrophages were isolated from them as previously described [ 31 ]. In brief, 150 million peripheral blood mononuclear cells (PBMC) were plated in RPMI1640 (Thermo Fisher Scientific, #31870, Waltham, MA, USA), containing 1% Glutamax (Thermo Fisher Scientific, #35050038) and 0.1% Primocin (InvivoGen, #ant-pm-2, San Diego, CA, USA) in cell culture Petri dishes (Corning, #430167, Corning, NY, USA) for at least 1 h in a 37 °C 5% CO 2 incubator to promote attachment.…”
Section: Methodsmentioning
confidence: 99%
“…Adherent cells were cultured in the medium described above containing an additional 1% heat inactivated human plasma and 50 ng/mL M-CSF (ImmunoTools, #11343113, Friesoythe, Germany). Generation of heat inactivated human plasma was prepared as previously described [ 31 ]. After 5–7 days, “M0” macrophages were collected with Accutase (Thermo Fisher Scientific, #00-4555-56) and replated at 10 6 cells/well in 6 well plates (Corning, #3506).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated plasma‐polarized macrophages can inhibit cell viability, EMT, and cancer stemness in glioblastoma multiforme 43 . In 2022, Trzeciak discovered that M0 resting macrophages treated with CAP exhibited an increase in the M2 phenotype, focusing on the effects and changes of plasma‐induced oxidative stress on macrophages in the melanoma tumor microenvironment 44 . Different plasma treatment parameters and application scenarios, as shown in Table 2, may produce opposite outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Live-cell fluorescence imaging has been a valuable tool in the field of plasma medicine for investigating cellular and subcellular NTP treatment effects for different biomedical applications, including wound healing and cancer therapy [13][14][15][16]. Mounting evidence has demonstrated that the versatile medicinal properties of NTP arise from the diverse short-lived and persistent reactive species (e.g.…”
Section: Introductionmentioning
confidence: 99%